Genomics Reveal Population Structure and Intergeneric Hybridization in an Endangered South American Bird: Implications for Management and Conservation - Marisol Domínguez; Larissa S. Arantes; Pablo D. Lavinia; Nicole Bergjürgen; Agustin I. Casale; Pablo A. Fracas; Darío A. Lijtmaer; Pablo Tubaro; Sarah Sparmann; Susan Mbedi; Camila Mazzoni; Bettina Mahler; et al. (Ecology and Evolution)
ABSTRACT Genomics is an invaluable tool for conservation, particularly for endangered species impacted by wildlife trafficking. This study uses genomic data to provide new insights to aid conservation and management of endangered species, using as a case study the Yellow cardinal (Gubernatrix cristata), a bird endemic to southern South America severely affected by illegal trade and the transformation of its natural habitat. We explore population structure within the Yellow cardinal, delimiting management units and describing connectivity among them. Additionally, we develop and assess the accuracy of a panel of 189 informative SNPs, and demonstrate how these can reliably assign confiscated individuals to one of the management units established. Lastly, we assess hybridization between the Yellow cardinal and the Diuca finch (Diuca diuca), which is reported to occur in regions of sympatry. We confirm that hybridization occurs, although it is not as common as previously thought, and that hybrids might be fertile, as we found evidence of backcrossing with Yellow cardinals. We discuss the implications of this introgression for the evolution and conservation of Yellow cardinals. Our study provides new, valuable information that can guide conservation efforts, comprising a test case for the use of genomics in combating illegal trafficking, with potential application beyond the case of the Yellow cardinal.